Implementation of Akhlaqul Karimah Through Islamic Religious Education Approach In Early Children - Imam Tabroni; Sania Rahmania (PT FORMOSA CENDEKIA GLOBAL, 2022)
Akhlak are the concern of people everywhere, both in advanced societies and underdeveloped societies, because if in a society there are many people whose Akhlak have been damaged, the society will be damaged. This shows that the position of morality in human life occupies a very important position, both as individuals and as members of society and the nation.